Evaluation of genetic diversity in long hair Nagaland goat Sumi-Ne - VERMA, N K; AGGARWAL, R A K; SHIVAHRE, P R; SHARMA, REKHA; SAVINO, N (The Indian Journal of Animal Sciences, 2019)
The long hair Nagaland goat (LHNG) registered by the name Sumi-Ne (Accession No. ‘INDIA_GOAT_1400_ SUMI-NE_06028’) are mainly found in Zunehoboto and Tuensang districts whereas their number is very less in Kiphire, Phek and other districts of Nagaland. The long hair goat, as the name indicates, is distinguished from other goat populations of NEH region by the presence of long silky hair in males and are reared by Sumi tribe people under extensive and semi-extensive system of management. These goats are predominantly of black (head & neck) and white (remaining parts) colour. The long hair of these goats are of commercial utility for the tribal people. An attempt was made to characterize these goats genetically using microsatellite markers (23). All the 23 loci investigated were found polymorphic. Polymorphic information content ranged from 0.044 (OarJMP29) to 0.789 (ILSTS058) with an average 0.465±0.048. The total number of alleles observed across these microsatellite loci was 116. The number of alleles observed varied from 2 (OarJMP29) to 9 (ILSTS058) with an overall mean of 5.043±0.380. Effective number of alleles ranged from 1.048 (OarJMP29) to 5.414 (ILSTS058) with mean 2.576±0.285. The average observed heterozygosity within the population of LHNG ranged from 0.043 (ETH225) to 0.786 (OMHC1) with an average of 0.347±0.040, whereas expected heterozygosity ranged from 0.045 (OarLMP29) to 0.815 (ILSTS058) with an average of 0.499±0.050. The expected heterozygosity was significantly higher than observed heterozygosity at most of loci except ILSTS059, OarJMP29, ILSTS34, ILSTS022 and RM088. Shannon’s information index which measures the level of genetic diversity was sufficiently high with a mean of 1.008±0.105 and ranged from 0.110 (OarJMP29) to 1.811 (ILSTS058). The within population inbreeding estimates (FIS) varied from –0.467 (ILSTS022) to 0.780 (ETH225) with average 0.258±0.064. Only 5 loci (ILSTS059, OarJMP29, ILSTS34, ILSTS022, RM088) revealed negative F values indicating the absence of inbreeding at these loci. About 26% of the inbreeding was noticed in LHNG leading to moderate level of homozygosity in the population. The L-shaped mode-shift curve indicated absence of bottleneck (reduction in the effective population size) in the recent past. Long hair goats of Nagaland are genetically distant (0.636) from both Singharey and Black goats of Sikkim and many other goat breeds of the country. There is a need to establish a separate goat farm in the native tract for maintaining the genetic purity, their propagation and conservation.